Judicial Review of COVID-19 Restrictive Measures in the Czech Republic - Šimon Chvojka; Michal Kovalčík (Institutiones Administrationis, 2022)
The courts ought to be active players during the pandemic crisis to prevent the abuse of power, enhance the quality of the measures taken and their communication and contribute to increasing their legitimacy. The paper focuses on the Czech Constitutional Court and the Supreme Administrative Court (together with regional administrative courts) and assesses whether they lived up to this role. We found that the Constitutional Court was a passive player, which resulted from insufficient procedural legal norms and a formalistic approach by the court itself. On the other hand, the Supreme Administrative Court was – mainly due to a special procedural framework – an active player. Its case law has a real impact and prevents the executive power from making some faults, such as an obvious lack of legal basis or clearly insufficient reasoning.